Danièle Cochard - Emilio Lopez-Menchero - Anne Mortiaux - Chris Straetling - Ann Veronica Janssens - Michel François - Edith Dekyndt - Sylvie Ronflette - Angel Vergara - Bénédicte Henderick - Guy Rombouts - Monica Droste. - La Machine à Eau, Mons; Musée d'Ixelles, Ixelles; Musée d'Art Moderne et d'Art Contemporain, Liège; Brayer, Marie-Ange; Fermeuse, Colette; Gadenne, Norbert; Gilles, Stéphan; Tapta; Tilman, Etienne (Tournai : Centre de Recherche de la Fondation de la Tapisserie, 1997)
Cochard, Danièle ; Dekyndt, Edith ; Droste, Monica ; François, Michel ; Henderick, Bénédicte ; Janssens, Ann Veronica ; Lopez-Menchero, Emilio ; Mortiaux, Anne ; Rombouts, Guy ; Ronflette, Sylvie ; Straetling, Chris ; Vergara Santiago, Angel
biog. per kunstenaar
Frans
Cochard, Danièle ; Dekyndt, Edith ; Droste, Monica ; François, Michel ; Henderick, Bénédicte ; Janssens, Ann Veronica ; Lopez-Menchero, Emilio ; Mortiaux, Anne ; Rombouts, Guy ; Ronflette, Sylvie ; Straetling, Chris ; Vergara Santiago, Angel, La Machine à Eau, Mons, du 1 février au 6 avril 1997 ; Musée d'Ixelles, du 20 février au 29 mars 1997 ; Musée d'Art Moderne et d'Art Contemporain, Liège, du 7 juin au 6 juillet 1997
boek